A dinâmica entre governo e sociedade civil na gestão da assistência social: uma década de ação do Conselho Municipal de Assistência Social em Bauru - Soubhia, Ana Paula Cardia (2006)
This master s degree dissertation directs its analysis to the established relationships between the civil society and Government in the Municipal Council of Social Assistance (Conselho Municipal de Assistência Social) of Bauru, a city with approximately 340.000 inhabitants and located in Sao Paulo State, through a period of ten years (1995-2005). This dissertation is intended, thus, to present a study on the historic relationship between the State and the civil society. Therefore, it searches to analyze the level of democratization of the political management of social assistance in the sense of establishing a pattern of relationships that maintain it as a warranted social protection of citizenship rights policy, through the established relationships between the Government and the civil society, mediated by the Municipal Council of Social Assistance of Bauru. Interviews with the councilors were accomplished by this study, searching to focus on the thoughts of each councilor, their apprehension about the Council and the conceptualization about social assistance and the State, organized civil society and users relationship in the historical and democratic management of the institutionalization of social assistance in the city and the state ways made in each one s management period. Having as an analysis key the universalizing principle that prevails in social assistance, every citizen may become a user of such policy; this way, it is not possible to exclude the users of the civil society once they are integrant part of it, and, therefore, processing as well, in the social control of this policy. As a conclusive approach, it is distinguished that the democratic relationship in the political management of social assistance in the city of Bauru through the MCSA is an under-construction process, which needs the engagement of its social subjects State and civil society in the deepening of the absolute citizenship and requires radical changes in the political instances of power, the effective popular participation in the process of political decision making as well as the acknowledgment of the authority of the people which are essential mechanisms for its realization